2013
DOI: 10.7202/1020669ar
|View full text |Cite
|
Sign up to set email alerts
|

Le management interculturel comme processus de traduction. Le cas d’une entreprise béninoise

Abstract: La littérature scientifique propose plusieurs manières d’analyser l’influence des différences culturelles sur le management des organisations : on peut distinguer à cet égard les positions universaliste, contingente et interprétativiste. À partir de l’analyse d’un cas d’entreprise béninoise qui exporte sa production en Europe, nous examinons dans quelle mesure cette troisième voie permet d’expliquer l’atteinte de performances durables pour les organisations africaines. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
0
9
0
2
Order By: Relevance
“…Secondly, the cultural distance conception aims to establish some universal norms to evaluate cultures and practices. It obscures their permanent evolutions and the role of context (Adler, 1994;Pichault and Nizet, 2013). We consider that multiculturality defines the objective composition of the workgroup, but that cultural heterogeneity depends on the subjective perception of its members' characteristics in a specific situation.…”
Section: The Specific Problem Of Multicultural Workgroupsmentioning
confidence: 99%
“…Secondly, the cultural distance conception aims to establish some universal norms to evaluate cultures and practices. It obscures their permanent evolutions and the role of context (Adler, 1994;Pichault and Nizet, 2013). We consider that multiculturality defines the objective composition of the workgroup, but that cultural heterogeneity depends on the subjective perception of its members' characteristics in a specific situation.…”
Section: The Specific Problem Of Multicultural Workgroupsmentioning
confidence: 99%
“…Therefore, it is possible to postulate that staff recognition allows making a change according to the schedule set by the company management (planning process). This approach overlooks the fact that organizational change can be explained by other processes such as the political process, the interpretive process, the incremental process and the complex process (Vas and Ingham, 2002; Vas and Jaspart, 2010; Pichault, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…According to Van de Ven and Poole (1995), they represent theoretical models developed to understand how organizations change. In an attempt to understand the progression of change, some authors (Vas and Jaspart, 2010; Pichault, 2013) showed the coexistence and complementarity of these processes. The observed change was marked by the different characteristics falling within the various explanatory processes of change.…”
Section: Introductionmentioning
confidence: 99%
“…Chaque pays est composé d'un ensemble de communautés culturelles 1 avec autant de langues, de valeurs, de croyances, de coutumes, de mentalités, des modes de vie et de sociabilité spécifiques qui façonnent le comportement de chaque individu (Prinsloo, 2000;Mutabazi, 2001;Kamdem, 2002;Nizet et Pichault, 2007;Apitsa et Amine, 2014) . Cette spécificité a favorisé l'émergence de nombreuses publications qui traitent des différences culturelles dans la gestion des organisations en Afrique (D'Iribarne, 1986(D'Iribarne, , 1990(D'Iribarne, , 2003Hernandez, , 2007Allali, 2002;Henry, 2003Henry, , 2009Yanat et Scouarnec, 2005;Pichault et Nizet, 2013) . Les recherches ont démontré que l'Afrique est le lieu où la gestion des organisations présente des particularités indiscutables (Hofstede, 1980(Hofstede, , 2001Bourgoin, 1984;D'Iribarne, 1990D'Iribarne, , 2008; D'Iribarne 1.…”
unclassified
“…Certaines recherches analysent le lien entre culture et gestion des entreprises africaines et se focalisent sur les incidents critiques des traits culturels africains portés à la performance des entreprises (Hernandez, 2007;Nizet et Pichault, 2007) . D'autres évaluent plutôt les enjeux culturels africains par rapport au transfert des modèles occidentaux dans les organisations en Afrique (Allali, 2002;Frimousse et Peretti, 2005;Hernandez et Kamdem, 2007;Pichault et Nizet, 2013) . Au regard de l'ensemble des conclusions, nous observons que la dynamique culturelle à l'oeuvre au sein des entreprises est malgré tout très peu explorée .…”
unclassified